2018
DOI: 10.1021/acs.cgd.8b01332
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of ZnO Spherulites and Derivatives

Abstract: ZnO microparticles have been solvothermally synthesized from zinc acetate and formic acid. The resulting microspherulites consist of radially arranged nanorods which undergo a range of re-crystallisation pathways to produce particles with different terminal morphologies. Crystallisation on the particle surface results in hexagonal microdisc decorated hierarchical microspheres. These particles expose only the (0001) crystallographic plane of ZnO and further develop into a sea-urchin like morphology, when the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Since the NPs are roughly spherical, a large variety of crystallographic planes are presumably exposed to the CBD process [82]. Among these, polar surfaces are extremely chemically reactive [83,84] and have been found to be dominant surface nucleation sites for the growth of ZnO NWs in a solution [66]. To this regard, it has been observed that a high seed layer texture along the polar axis is necessary to obtain a high NW density [67,85,86].…”
Section: Resultsmentioning
confidence: 99%
“…Since the NPs are roughly spherical, a large variety of crystallographic planes are presumably exposed to the CBD process [82]. Among these, polar surfaces are extremely chemically reactive [83,84] and have been found to be dominant surface nucleation sites for the growth of ZnO NWs in a solution [66]. To this regard, it has been observed that a high seed layer texture along the polar axis is necessary to obtain a high NW density [67,85,86].…”
Section: Resultsmentioning
confidence: 99%
“…Many factors affect the formation of spherulites, such as supersaturation, impurities, crystal habits, and additives. , Nowadays, an increasing number of researchers seek to explore the preparation methods for spherulites. Some of them have used ions and polymers as additives to induce or promote spherulitic growth. With the in-depth studies on spherulites, the manufacture of spherulites is becoming increasingly advanced. For instance, the ions Mn 2+ , Ni 2+ , and Mg 2+ have been shown to promote the formation of calcium carbonate spheres, sodium hexametaphosphate has been found to mediate the core–shell spherulitic crystallization of lithium carbonate, gelatin has been used as an additive to induce the spherical formation process of l -tryptophan, and the presence of Mg and gelatin-agarose has been reported to influence the formation and architecture of mineral aggregate. .…”
Section: Introductionmentioning
confidence: 99%
“…A cross section SEM image of a spherulite shown in the inset of Figure a demonstrates a radial arrangement of microrods. The principal driving force of the ordering of the nanocrystallites into such a novel microstructure is probably a dipolar field as discussed in the previous reports on the formation of synthesized vaterite spherulites, naturally occurring aragonite spherulites, synthesized ZnO microspheres. , …”
Section: Resultsmentioning
confidence: 95%
“…The principal driving force of the ordering of the nanocrystallites into such a novel microstructure is probably dipolar field as discussed in the previous reports on the formation of synthesized vaterite spherulites, 16 naturally occurring aragonite spherulites, 17 synthesized ZnO microspheres. 27,28 It was noted that when the reaction time was increased to 24 h, the number of rhombohedral crystals significantly increased and the number of the spherulites decreased. The spherulites almost disappeared when the growth time was further increased to 48 h, leaving only rhombohedral crystals.…”
Section: Synthetic Spherulitesmentioning
confidence: 99%